El clima organizacional y su influencia en el desempeño laboral del personal administrativo de la municipalidad distrital de Sanagorán – 2017 - Valderrama Cruz, Gracia Karina (2019)
ABSTRACT The present investigation was developed with the purpose of determining in what way the organizational climate influences the work performance of the administrative staff of the District Municipality of Sanagorán - 2017. The type of study was non-experimental, design causal correlational, transversal. The population was constituted by the administrative personnel District Municipality of Sanagorán - 2017 that were 70, it was considered a universal sample because it was a small population, as an instrument two Likert scale questionnaires were used, the reliability test was done with Alfa of Cronbach, obtaining α = 0.832, for organizational climate and α = 0.868, for work performance considered as good reliability; the software SPSS version 24 was used to process the information. After processing the data, the result obtained with the correlation coefficient Spearman was r = 0.352, indicating a low direct correlation between organizational climate and work performance, with p = 0.003; lower than the level of standard significance α = 0.01, that is, the organizational climate has a significant influence on the work performance of the administrative staff of the District Municipality of Sanagoran - 2017; therefore, the research hypothesis is accepted. Likewise, the organizational climate is located at a regular level with 94.3%, just as the work performance is at a regular level with 50%. It is recommended to practice a participative organizational climate, open with a flexible structure, motivate the staff to find new ways of doing their work, maintain an active communication, given the opportunity and facilities to the staff, so that they continue to develop professionally, have a system to monitor and control activities, indicators and goals to have the possibility of amending delays and making better decisions to achieve the objectives set as an institution, and design an annual training program to improve work performance.